2013
DOI: 10.2217/imt.13.133
|View full text |Cite
|
Sign up to set email alerts
|

Is Faster Safer? Cluster Versus Short Conventional Subcutaneous Allergen Immunotherapy

Abstract: The safety profile of the cluster regimen supports the use of accelerated SCIT schedules with IR-standardized allergen extracts compared with short conventional schedules, particularly if similar extracts and application methods are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…15,17 Though our study was not completely consistent with other studies, we indeed observed this result. Besides, our result was in accordance with Quiralte et al' study, 16 which also found that the incidence of adverse reactions with cluster schedules is lower than with conventional schedules. On the one hand, we thought it was related to the sample size.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…15,17 Though our study was not completely consistent with other studies, we indeed observed this result. Besides, our result was in accordance with Quiralte et al' study, 16 which also found that the incidence of adverse reactions with cluster schedules is lower than with conventional schedules. On the one hand, we thought it was related to the sample size.…”
Section: Discussionsupporting
confidence: 92%
“…This has the advantage of a reduced number of hospital visits, which reduces the time and expense required. Several studies have compared the efficacy and safety of cluster schedules versus conventional approaches, [15][16][17] but few reports on the efficacy and safety of the 2 SIT regimens in the initial stage have been published. In this randomized, open-label study, we compared the efficacy and safety of the build-up phase of the cluster schedule with that of the conventional schedule.…”
Section: Introductionmentioning
confidence: 99%
“…Fatal and nearfatal reactions in AIT tend to occur in the first 30 minutes, but not exclusively. [24][25][26] The inclusion of a rigid definition of time to onset might overlook severe reactions occurring not that acutely, as has been previously discussed, although all severe reactions in EASSI occurred 10 to 20 minutes after AIT administration.…”
Section: Discussionmentioning
confidence: 99%
“…This study retrospectively assessed the safety and applicability of a cluster regimen in clinical routine for SCIT with HDM in a pediatric population of 21 patients with allergic asthma and/or allergic rhinitis. In the vast majority, AEs were mild and localized with a red swelling of less than 5 cm in diameter at injection sites, which is considered as common during SCIT and clinically not relevant [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Systemic AEs and major local AEs were usually mild and occurred in 3 patients (14.3%) each.…”
Section: Discussionmentioning
confidence: 99%
“…risk of adverse events (AEs) than conventional updosing regimens [2][3][4][5]. Cluster and even rush regimens have been introduced into clinical routine for hymenoptera venom SCIT [6], but are less commonly used for aeroallergens such as house dust mites (HDM) [2] despite a safety profile comparable to conventional SCIT [3,7,8].…”
mentioning
confidence: 99%